2022
DOI: 10.2147/eb.s313161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tACS-Like Electrical Stimulation on Correlated Firing of Retinal Ganglion Cells: Part III

Abstract: Purpose: Transcranial alternating current stimulation (tACS) is a stimulation protocol used for learning enhancement and mitigation of cognitive dysfunction. Correlated firing has been postulated to be a meta-code that links neuronal spike responses associated with a single entity and may be an important component of high-level cognitive functions. Thus, changes in the covariance firing structure of CNS neurons such as retinal ganglion cells are one potential mechanism by which tACS can exert its effects. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Seminal experimental [ 15 , 16 ] and computational [ 46 ] studies have reported no significant increase in firing rate during tACS, in contrast to our simulations where elevated spiking was observed. Experimental results remain however conflicted [ 21 , 53 55 ] and the nature of such disparity remains to be fully elucidated. We have deliberately conducted our simulations in a regime of high tACS amplitude sufficient to cause depolarization of neurons, to amplify resulting STDP-induced synaptic changes and evaluate their dependence on MTC disparity at temporal scales accessible by our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal experimental [ 15 , 16 ] and computational [ 46 ] studies have reported no significant increase in firing rate during tACS, in contrast to our simulations where elevated spiking was observed. Experimental results remain however conflicted [ 21 , 53 55 ] and the nature of such disparity remains to be fully elucidated. We have deliberately conducted our simulations in a regime of high tACS amplitude sufficient to cause depolarization of neurons, to amplify resulting STDP-induced synaptic changes and evaluate their dependence on MTC disparity at temporal scales accessible by our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…This paper does not report on hypothesized tACS effects on synchronous firing by entraining neural activity, as reported by Vieira et al 16 This issue is addressed in a companion paper comparing the effects of tACS on correlated ganglion cell firing during simultaneous microelectrode array recordings. 43 …”
Section: Limitations and Future Directionsmentioning
confidence: 99%